Make your own : 120+ minimally processed, oil-free, wheat-free, sugar-free, plant-based recipes - Benton, Javant (Balance, 2026)
"Healthy cooking continues to trend: many people-vegans and omnivores alike-are looking for wholesome, easy recipes to start or sustain their plant-based journeys while avoiding highly processed store bought meat replacements. Social media star Javant Benton found himself on a similar search at the start of his journey. Prediabetic and 85 pounds overweight, he needed to make a change-fast. Now, he shares the recipes that helped him improve his health and that of his many followers. From staples like vegan ground round, crispy no-bacon mushrooms, MaYO (Make-Your-Own mayo) to Greek burgers and spinach pear and pistachio salad, as well as an array of delicious desserts, Javant shares recipes along with tips and strategies to inspire and empower readers to reach their health goals by getting in the kitchen and making their own"-- Provided by publisher.